Persistent organic pollutants - Hutzinger, O. (Springer, 2003)
Since the mid 1990s, legal action to eliminate persistent organic pollutants (POPs) has started resulting in a global Convention on POPs, the Stockholm Convention, and a regional Protocol under the Convention on Long-Range Transboundary Air Pollution (UN-ECE LRTAP Convention). POPs are characterized by long half-lives, persistence in the environment, they undergo long-range transport, accumulate in the environment and in biota, and they are toxic. The combination of these characteristics makes them a threat at the global level. This book makes the reader familiar with the goals of these two conventions, lays out characteristics of these compounds, presents results from case studies and addresses inventories, levels in humans and the environment as well as technologies to destroy them.